870 SISPA Corps Cadet Officer receives Second Lieutenant commissioning - Mimi Rabita, Abdul Wahit (2021)
KUANTAN, 7 November 2021 – A total of 870 SISPA Corps Cadet Officers from 24 Higher Education Institutions (HEI) and one Institute of Teacher Education (IPG) received commissioning as Junior Lieutenants (PA) in conjunction with the 12th Civil Defence Student Corps (SISPA Corps) National Commissioning Ceremony 2021.